Staged revascularization vs. culprit-only percutaneous coronary intervention for multivessel disease in elderly patients with ST-segment elevation myocardial infarction - Lang, Jiachun; Wang, Chen; Wang, Le; Zhang, Jingxia; Hu, Yuecheng; Sun, Huajun; Cong, Hongliang; Liu, Yin (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective: Studies have highlighted the significant role of staged percutaneous coronary intervention (PCI) for multivessel disease (MVD) in patients who suffer from ST-elevation myocardial infarction (STEMI). However, the relative benefit of staged PCI versus culprit-only PCI for MVD in elderly patients with STEMI remains undetermined. The present study thus contrasted the clinical outcomes of staged PCI versus culprit-only PCI in this cohort. Methods: From January 2014 to September 2019, 617 patients aged ≥ 65 years with STEMI and MVD who had underwent primary PCI of culprit vessels within 12 hours from symptom onset were enrolled. Then they were categorized into staged-PCI group and culprit-only PCI group according to different intervention strategies. Propensity score matching (PSM) was conducted to adjust the confounding between the two groups. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), which was a composite of all-cause death, cardiac death, recurrent myocardial infarction (MI), stroke and ischemia-driven revascularization. Results: During a mean follow-up of 56 months, 209 patients suffered from MACCE and 119 patients died. Staged revascularization was associated with lower risk of MACCE, all-cause death and cardiac death compared with the culprit-only PCI in either overall patients or propensity-matched cohorts. In contrast, no significant difference was found between the two groups in stroke and ischemia-driven revascularization. Moreover, multivariate cox regression analysis showed that staged PCI was a significant predictor for lower incidence of MACCE and all-cause death. Conclusion: In elderly patients with STEMI and MVD, staged PCI is superior to the revascularization strategy of culprit-only PCI.